Acute effects of different balance exercise types on selected measures of physical fitness in youth female volleyball players - Hammami, R.; Chaabene, H.; Kharrat, F.; Werfelli, H.; Duncan, M.; Rebai, H.; Granacher, U. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background: 'Earlier studies have shown that balance training (BT) has the potential to induce performance enhancements in selected components of physical fitness (i.e., balance, muscle strength, power, speed). While there is ample evidence on the long-term effects of BT on components of physical fitness in youth, less is known on the short-term or acute effects of single BT sessions on selected measures of physical fitness. Objective: To examine the acute effects of different balance exercise types on balance, change-of-direction (CoD) speed, and jump performance in youth female volleyball players. Methods: Eleven female players aged 14 years participated in this study. Three types of balance exercises (i.e., anterior, posterolateral, rotational type) were conducted in randomized order. For each exercise, 3 sets including 5 repetitions were performed. Before and after the performance of the balance exercises, participants were tested for their static balance (center of pressure surface area [CoP SA] and velocity [CoP V]) on foam and firm surfaces, CoD speed (T-Half test), and vertical jump height (countermovement jump [CMJ] height). A 3 (condition: anterior, mediolateral, rotational balance exercise type) × 2 (time: pre, post) analysis of variance was computed with repeated measures on time. Results: Findings showed no significant condition × time interactions for all outcome measures (p > 0.05). However, there were small main effects of time for CoP SA on firm and foam surfaces (both d = 0.38; all p < 0.05) with no effect for CoP V on both surface conditions (p > 0.05). For CoD speed, findings showed a large main effect of time (d = 0.91; p < 0.001). However, for CMJ height, no main effect of time was observed (p > 0.05). Conclusions: Overall, our results indicated small-to-large changes in balance and CoD speed performances but not in CMJ height in youth female volleyball players, regardless of the balance exercise type. Accordingly, it is recommended to regularly integrate balance exercises before the performance of sport-specific training to optimize performance development in youth female volleyball players.